2022
DOI: 10.3390/vetsci9080434
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Dairy Cattle for Female Fertility and Production in the Age of Genomics

Abstract: Phenotypic and genetic changes for female fertility and production traits in the Israeli Holstein population over the last three decades were studied in order to determine if long term selection has resulted in reduced heritability and negative genetic correlations. Annual means for conception status, defined as the inverse of the number of inseminations to conception in percent, decreased from 55.6 for cows born in 1983 to 46.5 for cows born in 2018. Mean estimated breeding values increased by 1.8% for cow bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Negative relationship between milk production and reproduction of dairy cows is well known (Lucy, 2019). In Israel annual means for conception status (the inverse of the number of inseminations to conception in percent) decreased from 55.6 for cows born in 1983 to 46.5 for cows born in 2018 (Weller et al, 2022). Genetic nature of antagonism between fertility and milk production was confirmed in the study of (Ma b et al, 2019).…”
Section: Descriptive Statisticsmentioning
confidence: 81%
“…Negative relationship between milk production and reproduction of dairy cows is well known (Lucy, 2019). In Israel annual means for conception status (the inverse of the number of inseminations to conception in percent) decreased from 55.6 for cows born in 1983 to 46.5 for cows born in 2018 (Weller et al, 2022). Genetic nature of antagonism between fertility and milk production was confirmed in the study of (Ma b et al, 2019).…”
Section: Descriptive Statisticsmentioning
confidence: 81%
“…In the current study, the prevalence of the B allele has more than doubled to around 40% in the entire population. This strong increase stems from the advantage of the B allele for protein content, which is the major objective in the Israeli breeding index [ 29 ]. In contrast, the prevalence of the E allele has decreased from about 6% to 2.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the low level of heritability of reproduction indicators, including the service period, and the presence of an unfavourable genetic relationship between them and the milk productivity of cows does not mean that their genetic improvement by breeding methods is impossible. Weller et al (2022) analysed phenotypic and genetic changes in milk productivity (milk yield, fat, and protein) and reproduction (fertilisation status, which is the inverse of the number of inseminations per fertilisation, expressed as a percentage) in the Holstein livestock population of Israel for the period from 1980 to 2018. The authors identified that in parallel with the increase in milk productivity, there was a decrease in the status of fertilisation from 55.6% in 1983 to 46.5% in 2018, but the average assessment of the breeding value of animals by fertilisation status increased from -1.9 to -0.1.…”
Section: Table 5 Estimates Of the Breeding Value Of Breeding Bulls By...mentioning
confidence: 99%